Elliptic problems with nonmonotone discontinuities at resonance. (23rd September 2002) - Nikolaos, Halidias
Abstract : Using the critical point theory of Chang (1981) for locally Lipschitz functionals, we prove an existence theorem for some elliptic problems at resonance with no Carathéodory forcing term. Elliptic problems with nonmonotone discontinuities at resonance (Erratum) dx.doi.org/10.1155/S108533750430905X